FAKTOR – FAKTOR YANG MEMPENGARUHI PRODUKSI USAHA PETERNAKAN BROILER POLA KEMITRAAN DI KABUPATEN BLITAR - Ariani Trisna Murti; Erik Priyo Santoso (Universitas Tribhuwana Tunggadewi, 2017)
This research was conducted a many of broiler farmers who partnered with PT. SMS in Blitar district. The data collection was conducted during June – July 2014 that focus on the elasticity of the business production of a farm broiler a partnership system PT. SMS. Research method used is a method of survey sample with the determination of the sampling method purposively namely broiler chicken farmers who implement the program partnership with PT. SMS Indonesia. The number of the overall sample can be taken a number of the population of 60 people as representatives of farmers. Variable research used is the number of broiler, the purchase of DOC, the work force, the cost of feed, vitamins and medicine, electricity, mortality, the cost of production, and the number of family members. Data analysis conducted includes data qualitative and quantitative. Quantitative analysis is the calculation of the production costs, revenues, and income. Qualitative analysis of the aims to calculate factors affecting business production of the use of Cobb-Douglasregression analysis. Data processing from the result of this research conducted using the SPSS version 16,0. The research results show that mortalitas and its cost of production a factor of production that is very significant to affect elastic and wreak on the number of businesses production. Conclusion shows that 1 ) mortalitas and its cost of production is of factors affect elastic and wreak on the amount of the production of 2 ) the number of cattle, the purchase of d.o.c, the cost of feed, and its cost of production is the factors that are not elastic against the production of business. Advice in research to 1 ) farmers more selective in the election of the seeds of doc who will be maintained and noticed a big factor cause of death of livestock so that the number can be suppressed mortalitas 2 ) the use of the factors of production and business capital is more efficient, because with the use of production factors efficient will affect the amount of income production